Influência da intensidade do laser nos mapas de atividade do biospeckle - Reis, Renan Oliveira (2015)
The dynamic speckle laser is an optical technique that uses interference patterns generated by laser illumination of a surface to obtain the modification level of this pattern over time. Thus, speckle grains present in the illuminated sample change their form and intensity according to the position of light scatters. In order to measure the activity of the illuminated material by means of modifications in speckle patterns, we use computer tools that present graphical and numerical output. To obtain the speckle patterns, laser intensity is set according to the amount of information obtained from the layers near the surface. The irregularities of biological materials cause the biospeckle laser technique to be sensitive and dependent on details in order to obtain a quality analysis. Light intensity is an important element for the formation of speckle patterns. To contribute for this technique, this study had the objective of investigating the influence of light over images obtained by laser biospeckle. For the evaluation of lighting, different laser intensity were applied to samples of biological material. The speckle patterns were analysed using the MI, AVD, SD, DG and Fujii methods. Other tests were performed to improve the independence of the lighting in a homogeneous sample. A new standardization for the MI and AVD methods has been proposed and tested using drying paint. The results showed that the variation of light intensity is important for biospeckle laser data, and the standardization proposal showed improvements concerning the independence of the laser intensity.